Collaborative peer feedback in L2 writing: Affective, behavioral, cognitive, and social engagement - Chen, Wenxue; Liu, Donghong; Lin, Cancan (Frontiers in Psychology, 2023)
The recent two decades have witnessed a greater interest in L2 writing research to explore how individual learners engage with and participate in peer feedback. However, not much attention has been directed to peer feedback in the collaborative format, despite the fact that peer collaboration can enable learners to draw on their respective strengths and pool their knowledge. In this qualitative study, we adopted an educational psychological perspective to discover the intricate nature of learners working together to give anonymous feedback to their peers. In addition to learners’ cognitive engagement with the correction and revision process, we also investigated learners’ affective, behavioral, and social engagement in collaborative peer feedback. The findings show that, although learners can cognitively engage with the task by identifying a number of language-related problems and providing feedback, their affective, behavioral, and social engagement differed considerably. While some participants’ engagement was relatively extensive, especially in the affective and social aspect, others’ engagement was at a relatively limited level, characterized by negative emotions and low mutuality in peer interaction. The unpleasant task experience affected their attitudes toward collaborative peer feedback activities and their willingness to participate in subsequent tasks.